OP0090 The human safe NLRP3 inflammasome inhibitor OLT1177 suppresses joint inflammation in murine models of experimental arthritis. (15th June 2017) - Marchetti, C; Swartzwelter, B; Koenders, MI; Dinarello, CA; Joosten, LA
Abstract : Background: NLRP3 is an essential component of the inflammasome, an intracellular macromolecular complex, which activates caspase-1 for the processing and release of active IL-1β and IL-18. Activation of the NLRP3 inflammasome takes place in inflammatory joint diseases, including gout. Although inhibition of IL-1β with either the IL-1 receptor antagonist anakinra or canakinumab, a neutralizing monoclonal antibody for IL-1β is highly effective for reducing the gout flares, a clinical need remains for a safe, oral treatment of recurrent gout flares refractory to standard of care. The small orally active and safe β-sulfonyl nitrile molecule OLT1177 is a specific inhibitor of the NLRP3 inflammasome, and currently being evaluated in a Phase 2 study for the treatment of acute gout flares. Objectives: To investigate the anti-inflammatory effect of NLRP3 inflammasome inhibitor OLT1177 in mouse models of acute joint inflammation. Methods: Two models of experimental arthritis were used in mice: zymosan- and monosodium urate (MSU)-induced arthritis. Knee joints of male C57BL/6 mice were injected intraarticularly with 180 μg heat-killed Zymosan or 300 μg of monosodium urate (MSU) crystals mixed with 200 μM C16.0 fatty acid and bovine serum albumin. Joints were assessed 24 and 4 hours after the zymosan or MSU/C16.0 injection, respectively, for clinical, histological and cytokine analyses. Results: Intraarticular Zymosan induced a severe joint swelling with neutrophil infiltration, high levels of synovial IL-1β, IL-6 and the neutrophil chemokine CXCL1. Treatment with OLT1177 induced reduction of joint swelling and neutrophil infiltration (P<0.0001 and P=0.006 respectively) and suppression of IL-1β and IL-6 by 55% and CXCL1 by 30% compared to mice treated with the vehicle. Four hours following intra-articular injection of MSU crystals, an elevated clinical score for knee joint inflammation was observed in vehicle-treated mice (Fig. 1 ). Oral treatment with OLT1177 showed reduction in joint inflammation as depicted in Fig. 1 a when compared to the vehicle group (P<0.0001). Histological analysis of the knee revealed suppression of the influx of inflammatory cells in the articular space with OLT1177 treatment (P<0.05; Fig. 1 b). Treatment with OLT1177 showed significant reduction in synovial tissue extracts for IL-1β (69%; P<0.001; Fig. 1 c); IL-6 (70%; P<0.001); CXCL1 (75%; P<0.001; Fig.1 d) and MPO (39%; P=0.006; Fig. 1 e). Mice were also treated with a single dose of OLT1177 1 hour after of intraarticular MSU and reduced joint swelling and IL-1β levels (P<0.05) were observed. OLT1177 treatment suppressed activation of the mitogen-activated protein kinases (MAPK) family, c-jun N-terminal kinase (JNK), which is implicated in the pathophysiology of rheumatoid arthritis and gout (Fig. 1 f). Conclusions: The orally active molecule OLT1177 is a potent inhibitor of IL-1β-driven inflammatory arthritis, particularly in a model of acute gout. Considering the outstanding safety profile in humans, OLT1177 is a potential therapeutic strategy to target NLRP3-driven IL-1β-mediated disorders. Disclosure of Interest: C. Marchetti: None declared, B. Swartzwelter: None declared, M. Koenders: None declared, C. Dinarello Grant/research support from: Charles A. Dinarello serves on the Scientific Advisory Board of Olatec and receive compensation, L. Joosten Grant/research support from: Leo A. B. Joosten serves on the Scientific Advisory Board of Olatec and receive compensation